REST API and Message Broker RAbbitMQ for Integration of College Academic Information System - Ahmad Nur Ihsan Purwanto; Naufal Rasyid (Universitas Raharja, 2023)
Data integration is frequently used in a variety of applications and necessity. In the process of teaching and learning activities, STIMIK ESQ also has a Learning Management System (LMS), which is an e-learning system based on Moodle. For each class period, lecturers must complete a process to enter attendance information into the academic information system (AIS). A web-based system called AIS is used to track academic activity, class attendance, instructors, and student data. The lecturer must extract attendance information from the LMS in the form of an excel file, sort the information, and then categorize the data according to the study plan of each student. Manually entering attendance data takes between five and ten minutes. Processing all attendance for 12–15 courses takes 7–10 seconds after the assessment procedure. The STIMIK ESQ academic administrator downloads the excel file from AIS during the enrollment process and afterward creates a class on the LMS. The downloaded data is modified to fit the template specified for the LMS import procedure. Data entry for enrollment takes roughly 7 to 10 minutes. It takes between 10 and 15 seconds once the testing procedure is finished processing all courses for the odd semester of the 2020–2021 academic year. Data integration has been tested with utilizing RabbitMQ. The flexibility of REST, which can interface with two separate systems, and RabbitMQ, which can divide duties in processing a lot of data, are used in this research. In this study, the integration process is executed using a scheduler that will execute the integration process automatically.